Effects of the Administration of Bifidobacterium longum subsp. infantis CECT 7210 and Lactobacillus rhamnosus HN001 and Their Synbiotic Combination With Galacto-Oligosaccharides Against Enterotoxigenic Escherichia coli F4 in an Early Weaned Piglet Model - Rodríguez-Sorrento, Agustina; Castillejos, Lorena; López-Colom, Paola; Cifuentes-Orjuela, Gloria; Rodríguez-Palmero, María; Moreno-Muñoz, José Antonio; Luise, Diana; Trevisi, Paolo; Martín-Orúe, Susana María (Frontiers in Microbiology, 2021)
We evaluated the potential of a multi-strain probiotic (Bifidobacterium longum subsp. infantis CECT 7210 and Lactobacillus rhamnosus HN001) with or without galacto-oligosaccharides against enterotoxigenic Escherichia coli (ETEC) F4 infection in post-weaning pigs. Ninety-six piglets were distributed into thirty-two pens assigned to five treatments: one non-challenged (CTR+) and four challenged: control diet (CTR-), with probiotics (> 3 x 1010 CFU/kg body weight each, PRO), prebiotic (5%, PRE), or their combination (SYN). After one week, animals were orally inoculated with ETEC F4. Feed intake, weight, and clinical signs were recorded. On days 4 and 8 post-inoculation (PI), one animal per pen was euthanized and samples from blood, digesta, and tissues collected. Microbiological counts, ETEC F4 real time PCR (qPCR) quantification, fermentation products, serum biomarkers, ileal histomorphometry, and genotype for mucin 4 (MUC4) polymorphism were determined. Animals in the PRO group had similar enterobacteria and coliform numbers to the CTR+ group, and the ETEC F4 prevalence, number of mitotic cells at day 4 PI, and villus height at day 8 PI were between that observed in the CTR+ and CTR- groups. The PRO group exhibited reduced pig major acute-phase protein (Pig-MAP) levels on day 4 PI. The PRE diet group presented similar reductions in ETEC F4 and Pig-MAP, but there was no effect on microbial groups. The SYN group showed reduced faecal enterobacteria and coliform counts after the adaptation week but, after the inoculation, the SYN group showed lower performance and more animals with high ETEC F4 counts at day 8 PI. SYN treatment modified the colonic fermentation differently depending on the MUC4 polymorphism. These results confirm the potential of the probiotic strains and the prebiotic to fight ETEC F4 but do not show any synergy when administered together, at least in this animal model.